International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The seventh volume of the proceedings of the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. This collection contains 21 peer-reviewed papers on various transportation modes. Topics include: high-speed rail; multimodal regional systems; bus transit; electric aircraft; and airport planning.
Sponsored by Washington State Department of Transportation and the Transportation & Development Institute of the American Society of Civil Engineers,
Keywords: Railroads -- Maintenance and repair -- Congresses.; Airports -- Planning -- Congresses.; Airports -- Maintenance and repair -- Congresses.; Airplanes -- Technological innovations -- Congresses.; Local transit -- Management -- Congresses.; elektronické knihy; electronic books